2019
DOI: 10.26650/eor.201989121662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fracture resistance of roots-filled with various root canal sealers at different time periods

Abstract: Purpose: The reinforcement effect of 3 various root canal sealers (AH 26, MTA Plus sealer and BioRoot RCS) and gutta-percha at different time periods (1 week and 1 month) were evaluated in the present study. Materials and methods: Single-rooted, single-canalled, cracks-free 80 mandibular premolars were decoronated to a length of 13mm. Group PC (positive control, n=10): samples were left unprepared and unfilled. Seventy samples were prepared by using the ProTaper Rotary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 3 . Ten studies on the adaptation to root canal walls were included [ 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In comparison to the RBS, CSBs showed similar values of void volume marginal adaptation in five studies [ 32 , 36 , 37 , 38 , 39 ] whilst at the apical, mid, and coronal thirds, these values were high in three studies [ 31 , 35 , 41 ] and low in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics of the included studies are shown in Table 3 . Ten studies on the adaptation to root canal walls were included [ 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In comparison to the RBS, CSBs showed similar values of void volume marginal adaptation in five studies [ 32 , 36 , 37 , 38 , 39 ] whilst at the apical, mid, and coronal thirds, these values were high in three studies [ 31 , 35 , 41 ] and low in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies on fracture resistance were included [ 36 , 37 , 54 , 56 ] with values (FRV) mentioned in Newton unit and time intervals ranged from one week to a month. CSBs demonstrated similar FRVs when compated to RBS in three studies [ 36 , 37 , 56 ], whilst had superior values in one study [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this vital behavior, several studies have been published evaluating the dentinal tubule penetration of bioceramic sealers combined with Rhodamine B (Uzunoğlu Özyürek & Aktemur Türker, 2019; Wang et al, 2018). That is the reason why the use of a hydrophobic fluorophore associated with bioceramic sealers is fundamental.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the primary goal is to eliminate empty spaces into the root canal system using biologically compatible materials (Kok et al, 2012). Three‐dimensional root canal obturation must prevent or minimize the reinfection caused by microorganisms' leakage (Uzunoğlu Özyürek & Aktemur Türker, 2019) . Consequently, it must promote periapical healing (Pinheiro, Bramante, & Hussne, 2003).…”
Section: Introductionmentioning
confidence: 99%